If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (X + -6)(x + -2) + -5 = 0 Reorder the terms: (-6 + X)(x + -2) + -5 = 0 Reorder the terms: (-6 + X)(-2 + x) + -5 = 0 Multiply (-6 + X) * (-2 + x) (-6(-2 + x) + X(-2 + x)) + -5 = 0 ((-2 * -6 + x * -6) + X(-2 + x)) + -5 = 0 ((12 + -6x) + X(-2 + x)) + -5 = 0 (12 + -6x + (-2 * X + x * X)) + -5 = 0 (12 + -6x + (-2X + xX)) + -5 = 0 Reorder the terms: (12 + -2X + -6x + xX) + -5 = 0 (12 + -2X + -6x + xX) + -5 = 0 Reorder the terms: 12 + -5 + -2X + -6x + xX = 0 Combine like terms: 12 + -5 = 7 7 + -2X + -6x + xX = 0 Solving 7 + -2X + -6x + xX = 0 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -2X + -6x + -7 + xX = 0 + -7 Reorder the terms: 7 + -7 + -2X + -6x + xX = 0 + -7 Combine like terms: 7 + -7 = 0 0 + -2X + -6x + xX = 0 + -7 -2X + -6x + xX = 0 + -7 Combine like terms: 0 + -7 = -7 -2X + -6x + xX = -7 Add '6x' to each side of the equation. -2X + -6x + 6x + xX = -7 + 6x Combine like terms: -6x + 6x = 0 -2X + 0 + xX = -7 + 6x -2X + xX = -7 + 6x Reorder the terms: 7 + -2X + -6x + xX = -7 + 6x + 7 + -6x Reorder the terms: 7 + -2X + -6x + xX = -7 + 7 + 6x + -6x Combine like terms: -7 + 7 = 0 7 + -2X + -6x + xX = 0 + 6x + -6x 7 + -2X + -6x + xX = 6x + -6x Combine like terms: 6x + -6x = 0 7 + -2X + -6x + xX = 0 The solution to this equation could not be determined.
| 13t=20 | | 4s-20=9s | | x^3=(3.4/.25) | | 3y-4=33 | | (2-3d)(4-3d)=0 | | (4x-20)+(2x+8)=180 | | 4x^2+36x+4y^2+20y+42=0 | | (s-5)(s+3)=0 | | 125000+65.00x=0 | | 8x^2+8x-16=0 | | x/-31.8=-349.8 | | 4x^2-9y^2+40x-36y-8=0 | | 2x^2+16x+33=0 | | -4x-12-6x=10 | | 2/64=4/x | | 35=-3x+5 | | 4.1x+51.8*8=9.5-10.0 | | 5u+9=1 | | 3(3x-4)=20-(6x-10) | | log^3(x+6)=2 | | 9t^2-18t=0 | | 3n+6m-8=3m+m | | 3z=2 | | Y=6ln(12x) | | 3x+15=60-6x | | 7(-3x+8)-50=-8(-3x-9) | | x-(.15x)=350 | | 81=1/n^4 | | 8x-3=21-3x+x | | T=6D+7cm | | 2085000000+5550000x=25000000 | | 7x-(2x+50)=7 |